Al-Dirāsah al-Muqārinah ʿan Kafā'ah al-Tarjamah al-Taḥrīriyyah min al-Lugah al-ʿArabiyyah ilā al-Lughah al-Indūnisiyyah wa ʿAksuha - Mimi Jamilah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The research is conducting the objectives of (1) knowing the written translation ability of Indo-Arabic Intensive Arabic students at the An-Nur Islamic Boarding School Surabaya and (2) knowing the written translation abilities of Indo-Arabic Intensive Arabic students at the An-Nur Islamic Boarding School Surabaya (3) knowing the comparison between Indo-Arabic and Indo-Arabic Written Translation for Arabic Language Intensive Students at the Annur Islamic Boarding School Surabaya. In this research, the writer uses a quantitative data analysis method using paired sample T-test with an SPSS application. In this case, to compare the variable (x) Arabic-Indo translation ability (y) Arabic-Indo written translation ability and the comparison between written Arabic-Indo and Indo-Arabic translations for Intensive Arabic Students at the An-Nur Islamic Boarding School Surabaya. The correlation between the Arabic-Indo and Indo-Arabic translations is 0.548, which means a strong relationship. T count > t table (4,402 > 2.002) implies that Ho is rejected and Ha is accepted, meaning that there is a significant comparison between the ability of written Arabic-Indo and Indo-Arabic translations of the Intensive Arabic students at the An-Nur Islamic boarding school in Surabaya.تم إجراء البحث بأهداف: (1) معرفة القدرة على الترجمة الكتابية لطلاب اللغة العربية المكثفة في مدرسة النور الإسلامية الداخلية سورابايا (2) معرفة قدرات الترجمة التحريرية لطلاب اللغة العربية المكثفة في مدرسة النور الإسلامية الداخلية سورابايا (3) معرفة المقارنة بين الترجمة المكتوبة العربية لطلاب اللغة العربية المكثفة في مدرسة النور الإسلامية الداخلية سورابايا.. في هذا البحث ، يستخدم الكاتب طريقة تحليل البيانات الكمية باستخدام اختبار T للعينة المقترنة مع تطبيق SPSS. في هذه الحالة، لإيجاد مقارنة بين المتغير (x) قدرة الترجمة العربية-الهندية (y) القدرة على الترجمة المكتوبة العربية-الهندية والمقارنة بين الترجمة المكتوبة العربية-الهندية والهندية-العربية لطلاب اللغة العربية المكثفين في مدرسة النور الإسلامية الداخلية سورابايا. نتائج العلاقة بين الترجمتين العربية االإندونيىية والإندونيسية العربية هي 0.548 ، مما يعني أن هناك علاقة قوية ، و t عد > جدول t (4,402 > 2.002) ، مما يعني أن Ho مرفوض و Ha مقبول ، مما يعني أن هناك مقارنة كبيرة بين قدرة الترجمات العربية الهندية المكتوبة والهندية العربية. طلاب اللغة العربية المكثفون في مدرسة النور الإسلامية الداخلية في سورابايا.